Study of the relevance recreative aerobics exercises for women of the first mature age - Синиця, Тетяна; Шестерова, Людмила (Slobozhanskyi Herald of Science and Sport, 2017)
Tetiana Synytsya & Ludmila Shesterova Purpose: to establish the level and priority types of motor activity of women of the first adulthood. Material & Methods: in the course of the research the method of analysis and generalization of scientific and methodological literature was used. Results: it is established that for today there is a negative dynamics of the motor activity of the adult population of Ukraine, including women of the first adult age. A wide distribution in the system of their recovery is acquired by fitness technologies. Conclusion: analysis of studies has shown that the overwhelming majority of the female population of Ukraine has a low level of functional status, which is associated with a lack of time and a lack of desire to attend sports and health classes.